Metode Ketenangan Jiwa: Suatu Perbandingan antara al-Ghazali dan Sigmund Freud - Abd Syakur (Islamica: Jurnal Studi Keislaman, 2007)
Al-Ghazali and Freud are both concerned with the idea soul ?and within itthe notion of spiritual tranquility. They both argue that soul has qualities such as health, sickness, tranquility, worriness, and so on, which need to be managed and organized. However, the paradigm within which they speak of this notion is sharply different. For al-Ghaz?l?, the nature of soul is purity. Hence it tends to resort to virtue and avoid vice. Al-Ghaz?l? reckons that they are degrees of soul. But that which is tranquil is the highest degree of soul. This soul is what he ?borrowing the Qur?an- calls al-Nafs al-Mutma?innah (the tranquil soul). For Freud on the other hand, soul is an abstraction of man?s psychological and physical system. It is impulsive, and tends to seek material and physical satisfaction through sexual pleasure among others. Man in his view is a sexual being. He speaks of the structure of soul as having three categories, namely Id, Ego and Super-ego. It is Id -meaning lust- that dominates one?s soul. Man will acquire tranquility once he ?by means of his Ego and Super-ego- satisfied his Id. Conversely, a failure to satisfy Id will result in a psychological disorder. Hence the sharp contrast between al-Ghaz?l? and Freud. And it is about this contrast that this paper is concerned.